Penyusunan Strategi Pemerintah Kota Depok Penguatan Pelayanan Publik dengan Analisis SWOT - Rahayu, Amy Yayuk Sri; Khafian, Nidaan; Rahmayanti, Krisna Puji; Anza, Fikri Akbar; Afra, Syifa Amania (Jurnal Bina Praja, 2022)
The Depok City One-Stop Integrated and Investment Service (DPMPTSP) has an important role in providing public services in Depok City, especially in licensing services. During the last four years, the trend of investment realization in Depok City showed a positive trend in 2017 and 2018. During the pandemic, investment realization decreased due to the Covid-19 pandemic, but public demand for business permits is still quite high. Of the 77 types of licensing services, during the year 2021, 29,491 licenses have been issued. This shows that DPMPTSP has an important role in providing licensing services in Depok City. During the pandemic, the DPMPTSP requires strengthening licensing services related to increasing investment. The objectives of this research are; How is the strategy for strengthening licensing and non-licensing services at the DPMPTSP through an analysis of the organization's internal and external environmental factors. This study uses a post-positivism approach, which deductively uses the operationalization of the SWOT concept to find IFAS (Internal Factor Analysis Strategies) and EFAS (External Factor Analysis Strategies) scores. The analysis results show that DPMPTSP Depok City has the capital of strengths and opportunities with a convincing score. Thus, it is possible to do an expansion. However, on the other hand, it also has weaknesses and threats that are quite severe, so empowerment is needed in the field of excellent service, cooperation/networking, and increasing digitalization capacity. The recommendation given is that the strengthening of the Depok City DPMPTSP must be directed to minimize weaknesses and threats.